PHARMA COGNOSTIC EVALUATION AND DETAILED PHYTOCHEMICAL ANALYSIS OF HYMENODICTYON OBOVATUM BARK, AN ENDEMIC PLANT. - SHRUTI V. HEGDE,; GANESH R. HEGDE, (International Journal of Pharma and Bio Sciences, 2014)
Hymenodictyon obovatum Wall. in Roxb. (Rubiaceae) is a large endemic tree found in dry deciduous forests of Western Ghats. Bark of this plant is medicinal and used in Ayurvedic and Traditional system of medicine. The bark is febrifuge, antiperiodic, astringent, antimicrobial and also used to cure night blindness. Because of its medicinal properties, inner bark of this plant was subjected to study different pharmacognostical analysis. Microscopic studies have shown acicular and prismatic oxalate crystals, helical and pitted xylem vessels and biseriate medullary ray. The trail was made to study the difference between hot and cold bark extracts, which is found useful to know the importance of compound quality and exaction. Detailed phytochemical analysis and TLC was carried out and observed the presence of steroids, flavonoids, alkaloids, coumarin glycosides, tannins, phenols, vitamins and enzymes. The florescent compound found in TLC is predicted to be Scopoletin by GC-MS study.